Evaluation of the physical and chemical properties of andisol order soils under different production systems - Lazo-Bravo, Sergio Andrés; Mora-Tisoy, Jose Victor; Guerra-Acosta, Adriana del Socorro; Coral-Narváez, Estefany Valentina; Solarte-Benavides, Yina Estefany (Revista de Ciencias Agrícolas, 2025)
Analyzing the chemical and physical properties of the soil is essential to understanding its fertility and structure, which allows for improving the availability of nutrients and optimizing soil management, contributing to agricultural sustainability. This study was conducted in the Cascajo area of Santiago Putumayo. The objective was to determine the behavior of the chemical properties (cation exchange capacity - CEC, organic matter - OM, organic carbon - CO, pH, and nitrogen - N) and physical properties (apparent density, porosity, gravimetric humidity, and hydraulic conductivity) of andisol soils under different production systems. Three systems were evaluated: T1 - Secondary Forest system, T2 - Livestock system, and T3 - Agricultural system with blackberry cultivation (Rubus glaucus Benth). A completely randomized design (CRD) was employed, and soil sampling for chemical variables was done at a depth of 0 - 15 cm; however, they were done at depths of 0 - 15 and 15 - 30 cm for physical properties. The results indicate that the secondary forest system showed the most behavior in chemical variables CEC, MO, CO, and N with values of 10.02, 12.71, 7.42, and 0.64, as well as the highest values in the variables of gravimetric humidity with 250.14, porosity with 77.49, and hydraulic conductivity with 1.57. These findings highlight the importance of forests as systems capable of conserving soil properties more effectively that other production systems, due to their organic matter content, biological diversity, and minimal anthropic disturbance.